Human Thermal Comfort and Heat Stress in an Outdoor Urban Arid Environment: A Case Study - A. M. Abdel-Ghany; I. M. Al-Helal; M. R. Shady (Advances in Meteorology)
To protect humans from heat stress risks, thermal comfort and heat stress potential were evaluated under arid environment, which had never been made for such climate. The thermal indices THI, WBGT, PET, and UTCI were used to evaluate thermal comfort and heat stress. RayMan software model was used to estimate the PET, and the UTCI calculator was used for UTCI. Dry and wet bulb temperatures (Td, Tw), natural wet bulb temperature (Tnw), and globe temperature (Tg) were measured in a summer day to be used in the calculation. The results showed the following. (i) The thermal sensation and heat stress levels can be evaluated by either the PET or UTCI scales, and both are valid for extremely high temperature in the arid environment. (ii) In the comfort zone, around 75% of individuals would be satisfied with the surrounding environment and feel comfortable during the whole day. (iii) Persons are exposed to strong heat stress and would feel uncomfortable most of the daytime in summer. (iv) Heat fatigue is expected with prolonged exposure to sun light and activity. (v) During the daytime, humans should schedule their activities according to the highest permissible values of the WBGT to avoid thermal shock.